Swedish students at the University of Paris in the Middle Ages - Andrews, Robert; Ferm, Olle 1947- (Sällskapet Runica et mediævalia, Centre for Medieval Studies, Stockholm University, 2021)
This companion to the first volume of Swedish Students at the University of Paris in the Middle Ages narrows focus to a specific production of a Swedish academic and his Swedish scribe: an extract of Walter Burley’s De puritate artis logicae. Intended to contrast Burley’s realist logic with the revolutionary nominalist (or conceptualist) logic of William of Ockham, the work is highly derivative of Burley, yet offers interspersed defense of Ockhamist principles. Produced in 1329, it directly cites Ockham’s Summa logica of 1323, the oldest surviving copy of which is in the same manuscript. Indications are that it originated in a Parisian classroom setting, since it frequently urges auditors to conduct their own investigations. The edition here offers both corroborating and disconfirming evidence about some conjectures in the earlier edition of Burley and emendations proposed by later scholars. The single manuscript, copied at a Franciscan monastery in Sweden in 1340, but by unknown paths ending up in Erfurt, is of historical importance as evidence of the earliest dissemination of Ockham’s ideas and their first transmission to the intellectual hinterland of Sweden.